Electroacoustic Music Linked with Information Processing Research in Japan. - Osaka, Naotoshi (Contemporary Music Review)
This paper describes the electroacoustic music history of Japan since the late 1980s. This new music was originally created by traditional contemporary music composers. However, after the 1970s, the digital computer took over the primary role of the tape recorder for use in electroacoustic music, and composers could not keep up with the technological progress. Instead, composers of a younger generation who studied computer music in Europe began to emerge in the 1990s. They were quite active, and collaboration with music researchers in the computer science field established a longlasting community. The iconic event for Japan was the International Computer Music Conference, held in 1993 at Waseda University, Tokyo. This was successfully done in cooperation with the Kunitachi College of Music. After experiencing several such events, many researchers shifted their focus to music information processing research, while other musicians lost their interest in artistic computer music research. In the twenty-first century, individual composers are experiencing better and more convenient electroacoustic environments, including hardware and music software facilities. They are very active, and their interests range widely from pure electroacoustic music to multimedia sound art. However, an unified organisation has not yet been established for electroacoustic music, and this prevents Japan from achieving mutual understanding among composers.